Significados da deficiência física na perspectiva da pessoa que vivência, sua principal cuidadora e de profissionais de enfermagem - Lago, Daniely Beatrice Ribeiro do (2012)
The challenges experienced as nurse and manager, in an institution dedicated to the exclusive care of disabled persons motivated the development of this study, whose objective is to understand the meanings of physical deficiency from the perspective of the person suffering it, his/her main caregivers and nursing professionals. A quantitative-exploratory type of Case Study, based on the concepts of socio-anthropology, inserted into the research: "Meanings and senses of care in a chronic condition: a look from the socio-anthropological perspective". It was developed in Cuiabá, State of Mato Grosso and involved a public health institution of the State sphere; subjects of the study were five (05) persons: a 20 years old young woman with cerebral paralysis, her mother and exclusive caregivers, and three nursing professionals. The data were collected by interviews, during the period of July to August, 2011. The analysis was thematic and the results were organized in three categories: 1. The meanings present in the experience of, with and to the deficiency, where we discussed the meanings of the deficiency, its cause and interpretation; the meanings of the body, the society's look and the wheelchair, which were constructed and reconstructed with basis on the socially shared values. 2. The meanings of the daily life with the physically deficient person: the dependency, the autonomy, the social inclusion, the accessibility and the confrontation. 3. The meanings of care within the context of the physical deficiency, discussing the self-care, the own care, the familiar care, the maternal care, the professional care and the institutional care. The contributions of this study detach themselves by subsidizing reflections on the diversity of the forms of living, deepening the thematic of physical deficiency and incorporating social and cultural questions to this discussion. The preconception and the suffering within the context of physical deficiency articulates with the socio-historical heritage, the social barriers and the stigma being shared with the person suffering the same, by her main caregivers and by the nursing professionals caring exclusively of such persons. We highlight nursing as a profession with a potential to allow for new forms of managing the care of such persons, oriented to the integrity and the effectiveness in warranting the rights of disabled persons.